1993
DOI: 10.1111/j.1469-8986.1993.tb02058.x
|View full text |Cite
|
Sign up to set email alerts
|

The cold pressor test: Vascular and myocardial response patterns and their stability

Abstract: The purposes of the present study were to compare the cardiovascular response patterns evoked by three versions of the cold pressor test (either forehead stimulation or hand or foot immersion) and to determine the reproducibility of the responses over a 2-week interval. Blood pressure , heart rate, stroke volume, cardiac output, total peripheral resistance, and systolic time intervals were obtained during rest and during the cold pressor test in 42 young men. Across conditions, the pressor response was support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 39 publications
10
54
0
Order By: Relevance
“…14,15 However, limb and forehead cold pressor tasks tend to evoke divergent cardiac responses. Hand and foot cold pressor tasks typically elicit HR acceleration and some increase in myocardial performance (eg, PEP shortening), [11][12][13][14][15] whereas forehead cold pressor tasks tend to elicit HR deceleration, characteristic of the "dive reflex," with little change in myocardial performance. 11,12,14 The cardiac effects of whole-body CE involved HR deceleration and PEP shortening, suggesting an amalgam of the cardiac effects of limb and forehead cold stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 However, limb and forehead cold pressor tasks tend to evoke divergent cardiac responses. Hand and foot cold pressor tasks typically elicit HR acceleration and some increase in myocardial performance (eg, PEP shortening), [11][12][13][14][15] whereas forehead cold pressor tasks tend to elicit HR deceleration, characteristic of the "dive reflex," with little change in myocardial performance. 11,12,14 The cardiac effects of whole-body CE involved HR deceleration and PEP shortening, suggesting an amalgam of the cardiac effects of limb and forehead cold stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] One physical stressor frequently used in hypertension research is some variation of the cold pressor task, a potent stimulus for ␣-adrenergic vasoconstriction, which typically involves immersion of a limb in ice water or placement of a bag of ice water on the forehead. [11][12][13][14][15] A number of studies have shown that the magnitude of cardiovascular responses during cold pressor is related to future resting blood pressure (BP) and the development of hypertension. 16 -18 Furthermore, studies of both adults and children indicate that increases in total peripheral resistance (TPR) during various limb and forehead cold pressor tasks are greater in blacks than in whites, suggesting a possible racial difference in vascular reactivity to cold stress.…”
mentioning
confidence: 99%
“…The vascular mechanism constricts the vasculature, thereby increasing blood pressure much like constricting a hose increases water pressure. Specific stressors tend to elicit either myocardial or vascular responses, providing evidence of situational stereotypy (Saab et al 1992(Saab et al , 1993. Laboratory stressors that call for active coping strategies, such as giving a speech or performing mental arithmetic, require the participant to do something and are associated with myocardial responses.…”
Section: Biological Responses To Stressors Acute Stress Responsesmentioning
confidence: 99%
“…The hand was removed from the water after 1.5 minutes, and then re-emerged after 10 seconds to allow a total immersion time of three minutes with minimal discomfort. This task is characterized primarily by sympathetic α-adrenergic activation (Saab et al, 1993).…”
Section: Methodsmentioning
confidence: 99%